CLIFF-GRADS Science Collaboration Series 2020 - Thematic student session: Ruminant systems - Leahy, Sinead; Feyissa, Abraham A; Pepeeta, Bulelani; Martínez, Juan V; Arowolo, Muhammed (Global Research Alliance on Agricultural Greenhouse Gases (GRA) & CGIAR Research Program on Climate Change Agriculture and Food Security (CCAFS), 2020)
Learn more about the CLIFF-GRADS Program and Alumni: https://ccafs.cgiar.org/CLIFF-GRADS